Alkyl glycoside modified lithium iron phosphate and preparation method thereof
Through the use of double-layer carbon nanotube coating structure and alkyl glycosides, the problem of unevenness of carbon nanotube coating lithium iron phosphate is solved, significantly improving the conductivity and electrochemical performance of lithium battery materials, and improving the battery Charge and discharge efficiency and cycle life.
Patent Information
- Application Number
- CN202411453044.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing carbon nanotube coated lithium iron phosphate materials have unevenness during the coating process, which affects the modification effect and limits its application in lithium battery materials.
A double-layer carbon nanotube coated structure is adopted, where the inner layer is a single-wall carbon nanotube combined with alkyl glycosides, and the outer layer is a multi-wall carbon nanotube. Doping elements are deposited through chemical vapor phase to form a three-dimensional network structure, using alkyl groups As a dispersant and surfactant, glycosides improve the dispersion and coating effect of carbon nanotubes.
It significantly improves the electronic conductivity and electrochemical properties of the material, enhances the transmission speed of lithium ions, improves the charging and discharging efficiency of the battery, overcomes the problem of coating inequality, and improves the overall stability and cycle life of the material.
Smart Images

Figure CN119297243A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and in particular to an alkyl glycoside modified lithium iron phosphate and a preparation method thereof. Background Art
[0002] Lithium iron phosphate has the advantages of high energy density (3-4 times that of lead-acid batteries, 2.5 times that of nickel-cadmium batteries, and 1.8 times that of nickel-metal hydride batteries), long cycle life (more than 2,000 times), and low self-discharge rate, and is widely used in energy storage equipment, starting power supplies, and fixed power supplies. However, its electronic conductivity and ionic conductivity are poor, the diffusion rate of lithium ions is slow, and the actual specific capacity is low during rate charge and discharge. In order to solve this problem, the main methods currently used are carbon coating, metal and non-metal doping, and particle nano-crystallization.
[0003] Carbon coating is one of the ways to improve the conductivity and electrochemical properties of lithium iron phosphate, which can improve the material's cycle performance and charge-discharge performance. The carbon sources used for carbon coating include inorganic carbon sources (graphite, carbon black, etc.) and organic carbon sources (glucose, sucrose, etc.). Carbon nanotubes (CNTs), as an important carbon source for carbon coating, have excellent conductivity and can improve the conductivity of electrode materials; their high specific surface area helps to increase the number of active sites in electrode materials, thereby increasing the capacity and power density of the battery; carbon nanotubes have good chemical stability in a wide temperature range and are suitable as coating materials in high-temperature applications; the high thermal conductivity of carbon nanotubes helps to improve the thermal management performance of materials, especially in battery electrodes.
[0004] For example, the patent with publication number CN113991072A proposes a carbon nanotube / lithium iron phosphate composite material and its preparation method and application, in which lithium iron phosphate is grown in situ on carbon nanotubes and assembled into an integrated self-molding form. Carbon nanotubes act on the inside of lithium iron phosphate particles to form a three-dimensional synergistic conductive network, which effectively improves the conductivity of the material. The lithium-ion battery prepared based on this lithium iron phosphate positive electrode material can be exempted from adding a conductive agent in the homogenization stage, while ensuring the electrochemical properties such as capacity and rate of lithium-ion batteries, while reducing the processing difficulty and processing cost of the material pole piece. However, carbon nanotubes have few surface defects and lack active groups, and their dispersion ability in water and solvents is low; in addition, the carbon atoms in carbon nanotubes mainly form highly delocalized large π bonds in the form of SP2 hybridization, resulting in strong van der Waals forces between carbon nanotubes. At the same time, the specific surface area and aspect ratio of carbon nanotubes are relatively large, which seriously affects the dispersion in solvents. Generally speaking, carbon nanotubes are entangled with each other in the form of agglomerates, which affects the physical properties of the carbon nanotubes themselves and also affects the growth of lithium iron phosphate in the carbon nanotubes, greatly limiting its application in lithium battery materials. Summary of the invention
[0005] The invention provides an alkyl glycoside modified lithium iron phosphate and a preparation method thereof, so as to solve the technical problem that the conventional carbon nanotube coated lithium iron phosphate and the uneven coating of the carbon nanotube affect the modification effect.
[0006] The embodiments of the present invention are implemented by the following technical solutions:
[0007] An alkyl glycoside modified lithium iron phosphate comprises nano LiFePO4 and a double-layer carbon coating layer covering the nano LiFePO4; the inner carbon coating layer comprises single-walled carbon nanotubes and alkyl glycoside; the outer carbon coating layer comprises multi-walled carbon nanotubes and doping elements doped by chemical vapor deposition, and the outer carbon nanotubes and the inner carbon nanotubes are covalently bonded to form a three-dimensional network structure.
[0008] Preferably, in the inner single-walled carbon nanotube layer, the polar glycoside portion of the alkyl glycoside is adsorbed on the single-walled carbon nanotube, and the long-chain alkyl portion of the alkyl glycoside faces outward.
[0009] Preferably, in the modified lithium iron phosphate, the content of lithium iron phosphate is 88-94.5wt%, the content of carbon nanotubes is 4.5-6.5wt%, the content of alkyl glycoside is 0.05-5%, and the balance is doping elements; taking the content of carbon nanotubes as 100%, the content of single-walled carbon nanotubes is 30-40%, and the content of multi-walled carbon nanotubes is; the doping element is at least one of nitrogen, sulfur and boron.
[0010] A method for preparing alkyl glycoside modified lithium iron phosphate comprises the following steps:
[0011] S1: preparing stabilizer slurry: adding Fe2O3 and alkyl glycoside to a solvent and mixing to obtain a stabilizer solution;
[0012] S2: preparing a precursor slurry: adding carbon nanotubes, a lithium source and a phosphorus source into a stabilizer slurry to react to obtain a precursor slurry;
[0013] S3: preparing precursor powder: drying and sintering the precursor slurry to obtain precursor powder;
[0014] S4: preparing modified lithium iron phosphate: adding stabilizer slurry to the precursor powder to dilute it and then coating it on a substrate, introducing doping source gas and carbon source gas into a reactor, and obtaining modified lithium iron phosphate by chemical vapor deposition.
[0015] Preferably, in the step S1, based on 100wt% of the mass of the modified lithium iron phosphate, the added amount of the alkyl glycoside is 0.05-5%, and the added amount of the Fe2O3 is 50-60%.
[0016] Preferably, in step S2, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium phosphate and lithium dihydrogen phosphate, and the phosphorus source is at least one of phosphoric acid, lithium phosphate and lithium dihydrogen phosphate; the molar ratio of the lithium source to Fe2O3 lithium iron is 0.9 to 1:1, and the solid content of the precursor slurry is 30 to 40%.
[0017] Preferably, in step S3, the precursor slurry is dried by spray drying, and the spray drying air inlet temperature is 180°C to 220°C; the sintering temperature is 720°C to 800°C, and the sintering time is 4h to 12h.
[0018] Preferably, in step S4, the doping source gas is at least one of ammonia, diborane and hydrogen sulfide.
[0019] Preferably, the method further includes step S5: removing the catalyst Fe2O3: washing the modified lithium iron phosphate with an inorganic acid solution to remove Fe2O3.
[0020] An application of alkyl glycoside modified lithium iron phosphate as a positive electrode material for lithium batteries.
[0021] By adopting this technical solution, the double-layer carbon nanotube-coated nano LiFePO structure can significantly improve the electronic conductivity of the material. The inner single-walled carbon nanotube (SWCNT) and the outer multi-walled carbon nanotube (MWCNT) provide a continuous conductive path, which helps to speed up the transmission of lithium ions, thereby improving the charging and discharging efficiency of the battery.
[0022] Carbon nanotubes have few surface defects and lack of active groups, and their dispersion ability in water and solvents is low. In addition, the carbon atoms in carbon nanotubes mainly form highly delocalized large π bonds in the form of SP2 hybridization, resulting in strong van der Waals forces between carbon nanotubes. At the same time, the specific surface area and aspect ratio of carbon nanotubes are relatively large, which affects the physical properties of carbon nanotubes themselves, and further affects their uniform wrapping and dispersion when coated with LiFePO. The formation of a wrapped carbon layer has limited improvement on the performance of LiFePO. By adding alkyl glycoside to the stabilizer, the alkyl glycoside acts as a dispersant and a stabilizer at the same time, and is adsorbed on the surface of carbon nanotubes to prevent their aggregation and sedimentation. The polar glycoside part of alkyl glycoside connects to carbon nanotubes, making the surface of carbon nanotubes charged. The electrostatic repulsion prevents them from aggregating. The long-chain alkyl part of alkyl glycoside forms a three-dimensional barrier outward, increasing steric hindrance and preventing carbon nanotubes from aggregating. While effectively dispersing carbon nanotubes, alkyl glycoside is used to reduce surface tension and slurry viscosity, maintain a stable suspension state of carbon nanotubes, and facilitate subsequent drying and sintering. During the sintering process, the alkyl glycoside on the surface of carbon nanotubes is converted into a carbon layer, which is coated with LiFePO together with carbon nanotubes. Carbon nanotubes form a uniform single-walled carbon nanotube layer on the surface of LiFePO to wrap LiFePO, fully improving its corresponding electrochemical properties.
[0023] The outer multi-walled carbon nanotube layer is doped with doping elements through chemical vapor deposition (CVD), and forms bridges and branches with other carbon nanotube layers to build a three-dimensional network structure. This structure is conducive to improving the overall stability of the material and preventing structural damage caused by volume changes during the cycle. Doping elements (such as nitrogen, sulfur, and boron) can further optimize the electrochemical properties of the material and improve the surface activity of LiFePO, thereby increasing the capacity and cycle life of the battery.
[0024] On the basis of the inner single-walled carbon nanotube layer, a multi-walled carbon nanotube layer is deposited on the outer layer by chemical vapor deposition, and LiFePO is doped by chemical vapor deposition. On the basis of the uniform and stable coating of single-walled carbon nanotubes to stably improve the electrochemical properties of LiFePO, the density of carbon nanotubes can be further increased and their conductivity can be improved. At the same time, CVD is performed on the existing carbon nanotubes to grow more carbon nanotubes on their surface to increase the density of the network. Branches are grown on the side walls of carbon nanotubes by CVD to form a more complex three-dimensional network structure. Carbon nanotube bridge structures are grown between adjacent carbon nanotubes to enhance the electrical connection between them. Carbon materials are deposited on the surface of single-walled carbon nanotubes to form multi-walled carbon nanotubes, which increase the interaction between tube walls and the conductive path.
[0025] The stabilizer slurry contains iron oxide and alkyl glycoside. The excess iron oxide not only serves as a source of lithium iron phosphate, but also as a catalyst for vapor deposition during the chemical vapor deposition process. By using alkyl glycoside as a surfactant, not only can the dispersion and stability of the material be improved, but also its good biodegradability reduces the risk of environmental pollution.
[0026] The technical solution of the embodiment of the present invention has at least the following advantages and beneficial effects:
[0027] 1. The nano-LiFePO structure coated with double-layer carbon nanotubes of the present invention can significantly improve the electronic conductivity of the material; it helps to accelerate the transmission speed of lithium ions, thereby improving the charging and discharging efficiency of the battery;
[0028] 2. The present invention overcomes the technical problem that the uneven coating of carbon nanotubes during the coating process affects the modification effect;
[0029] 3. In the present invention, the alkyl glycoside acts as a dispersant and a surfactant to improve the coating effect of carbon nanotubes, and also acts as a carbon source to participate in the coating of LiFePO. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 A schematic diagram of the process flow of the method for preparing alkyl glycoside-modified lithium iron phosphate provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] An alkyl glycoside modified lithium iron phosphate comprises nano LiFePO4 and a double-layer carbon coating layer covering the nano LiFePO4; the inner carbon coating layer comprises single-walled carbon nanotubes and alkyl glycoside; the outer carbon coating layer comprises multi-walled carbon nanotubes and doping elements doped by chemical vapor deposition, and the outer carbon nanotubes and the inner carbon nanotubes are covalently bonded to form a three-dimensional network structure.
[0035] In this embodiment, in the inner single-walled carbon nanotube layer, the polar glycoside portion of the alkyl glycoside is adsorbed on the single-walled carbon nanotube, and the long-chain alkyl portion of the alkyl glycoside faces outward.
[0036] In this embodiment, in the modified lithium iron phosphate, the content of lithium iron phosphate is 90wt%, the content of carbon nanotubes is 5.5wt%, the content of alkyl glycoside is 3%, and the remainder is doping elements.
[0037] In this embodiment, the doping elements are nitrogen, sulfur and boron, and the doping ratio thereof is 1:1:1.
[0038] In this embodiment, the alkyl glycoside is alkyl glycoside APG0810.
[0039] A method for preparing alkyl glycoside modified lithium iron phosphate comprises the following steps:
[0040] S1: preparing a stabilizer slurry: adding Fe2O3 and alkyl polyglycoside to a solvent to obtain a stabilizer solution; based on the mass of the modified lithium iron phosphate being 100wt%, the addition amount of the alkyl polyglycoside is 3%, and the addition amount of the Fe2O3 is 50%;
[0041] S2: preparing a precursor slurry: adding carbon nanotubes, a lithium source and a phosphorus source to a stabilizer slurry to react to obtain a precursor slurry; the lithium source is lithium hydroxide, the phosphorus source is phosphoric acid; the molar ratio of the lithium source to Fe2O3 lithium iron is 0.95:1, and the solid content of the precursor slurry is 35%;
[0042] S3: Preparing precursor powder: drying and sintering the precursor slurry to obtain precursor powder; the precursor slurry is dried by spray drying, and the spray drying air inlet temperature is 180°C to 220°C; the sintering temperature is 720°C to 800°C, and the sintering time is 12h;
[0043] S4: preparing modified lithium iron phosphate: adding a small amount of stabilizer slurry to the precursor powder to dilute it and then coating it on a substrate, introducing a doping source gas and a carbon source gas into a reactor, and obtaining modified lithium iron phosphate by chemical vapor deposition; the doping gas is a mixed gas of ammonia, diborane and hydrogen sulfide in equal proportions; the carbon source gas is methane;
[0044] S5: Removing catalyst Fe2O3: Using dilute hydrochloric acid to wash the modified lithium iron phosphate to remove Fe2O3.
[0045] Example 2
[0046] The only difference between this embodiment and embodiment 1 is that in this embodiment, in the modified lithium iron phosphate, the content of lithium iron phosphate is 94.5wt%, the content of carbon nanotubes is 4.5wt%, the content of alkyl glycoside is 0.05%, and the balance is doping elements.
[0047] Example 3
[0048] The only difference between this embodiment and embodiment 1 is that in this embodiment, in the modified lithium iron phosphate, the content of lithium iron phosphate is 88wt%, the content of carbon nanotubes is 6.5wt%, the content of alkyl glycoside is 5%, and the balance is doping elements.
[0049] Example 4
[0050] The only difference between this embodiment and embodiment 1 is that in this embodiment, in the modified lithium iron phosphate, the content of lithium iron phosphate is 92wt%, the content of carbon nanotubes is 6.5wt%, the content of alkyl glycoside is 0.05%, and the balance is doping elements.
[0051] Example 5
[0052] The only difference between this embodiment and embodiment 1 is that in this embodiment, in the modified lithium iron phosphate, the content of lithium iron phosphate is 89wt%, the content of carbon nanotubes is 4.5wt%, the content of alkyl glycoside is 5%, and the balance is doping elements.
[0053] Example 6
[0054] The only difference between this embodiment and embodiment 1 is that, in this embodiment, the molar ratio of the lithium source to Fe2O3 lithium iron is 0.9:1.
[0055] Example 7
[0056] The only difference between this embodiment and embodiment 1 is that, in this embodiment, the molar ratio of the lithium source to Fe2O3 lithium iron is 1:1.
[0057] Comparative Example 1
[0058] The only difference between this comparative example and Example 1 is that in this comparative example, the modified lithium iron phosphate only includes an inner single-walled carbon nanotube layer.
[0059] In the preparation process, the precursor powder obtained in step S3 is alkyl glycoside-modified lithium iron phosphate.
[0060] Comparative Example 2
[0061] The only difference between this comparative example and Example 1 is that in this comparative example, the modified lithium iron phosphate only includes an outer multi-walled carbon nanotube layer.
[0062] During the preparation process, in step S2, no carbon nanotubes are added.
[0063] Comparative Example 3
[0064] The difference between this comparative example and Example 1 is that in this comparative example, in the preparation process of modified lithium iron phosphate, in the step S2, no alkyl glycoside is added.
[0065] The relevant data of the above embodiments and comparative examples are shown in Table 1 below:
[0066] Table 1. Data related to Examples 1-7 and Comparative Examples 1-3
[0067] Example Lithium iron phosphate (wt%) Carbon nanotubes (wt%) Alkyl glycoside (wt%) Lithium iron molar ratio Example 1 90 5.5 3 0.95:1 Example 2 94.5 4.5 0.05 0.95:1 Example 3 88 6.5 5 0.95:1 Example 4 92 6.5 0.05 0.95:1 Example 5 89 4.5 5 0.95:1 Example 6 90 5.5 3 0.9:1 Example 7 90 5.5 3 1:1 Comparative Example 1 93 2.5 3 0.95:1 Comparative Example 2 92.5 3 3 0.95:1 Comparative Example 3 90 5.5 0 0.95:1
[0068] For the above examples and comparative examples, lithium iron phosphate material was used as the positive electrode, metal lithium sheet was used as the negative electrode, Celgard2300 microporous membrane was used as the diaphragm, 1.0 mol / L LiPF6 ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1-5 (volume ratio) solution was used as the electrolyte, and R2025 button cells were assembled in a glove box. Electrochemical performance tests were performed. The relevant electrochemical data are shown in Table 2 below:
[0069] Table 2. Electrochemical experimental data related to Examples 1-7 and Comparative Examples 1-3
[0070]
[0071] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An alkyl glycoside modified lithium iron phosphate, characterized in that: It includes nano LiFePO4 and a double-layer carbon coating layer covering it; the inner carbon coating layer includes single-walled carbon nanotubes and alkyl glycoside; the outer carbon coating layer includes multi-walled carbon nanotubes and doping elements doped by chemical vapor deposition, and the outer carbon nanotubes and the inner carbon nanotubes are covalently bonded to form a three-dimensional network structure.
2. The alkyl glycoside-modified lithium iron phosphate according to claim 1, characterized in that: In the inner single-walled carbon nanotube layer, the polar glycoside part of the alkyl glycoside is adsorbed on the single-walled carbon nanotube, and the long-chain alkyl part of the alkyl glycoside faces outward.
3. The alkyl glycoside-modified lithium iron phosphate according to claim 1, characterized in that: In the modified lithium iron phosphate, the content of lithium iron phosphate is 88-94.5wt%, the content of carbon nanotubes is 4.5-6.5wt%, the content of alkyl glycoside is 0.05-5%, and the balance is doping elements; based on the content of carbon nanotubes as 100%, the content of single-walled carbon nanotubes is 30-40%, and the content of multi-walled carbon nanotubes is; the doping element is at least one of nitrogen, sulfur and boron.
4. A method for preparing the alkyl glycoside-modified lithium iron phosphate according to any one of claims 1 to 3, characterized in that: The steps include: S1: preparing stabilizer slurry: adding Fe2O3 and alkyl glycoside to a solvent and mixing to obtain a stabilizer solution; S2: preparing a precursor slurry: adding carbon nanotubes, a lithium source and a phosphorus source into a stabilizer slurry to react to obtain a precursor slurry; S3: preparing precursor powder: drying and sintering the precursor slurry to obtain precursor powder; S4: preparing modified lithium iron phosphate: adding stabilizer slurry to the precursor powder to dilute it and then coating it on a substrate, introducing doping source gas and carbon source gas into a reactor, and obtaining modified lithium iron phosphate by chemical vapor deposition.
5. The method for preparing an alkyl polyglycoside modified lithium iron phosphate according to claim 4, characterized in that: In the step S1, based on 100wt% of the mass of the modified lithium iron phosphate, the added amount of the alkyl polyglycoside is 0.05-5%, and the added amount of the Fe2O3 is 50-60%.
6. The method for preparing an alkyl glycoside modified lithium iron phosphate according to claim 4, characterized in that: In step S2, the lithium source is at least one of lithium hydroxide, lithium carbonate, lithium phosphate and lithium dihydrogen phosphate, and the phosphorus source is at least one of phosphoric acid, lithium phosphate and lithium dihydrogen phosphate; the molar ratio of the lithium source to Fe2O3 lithium iron is 0.9 to 1:1, and the solid content of the precursor slurry is 30 to 40%.
7. The method for preparing an alkyl glycoside modified lithium iron phosphate according to claim 4, characterized in that: In the step S3, the precursor slurry is dried by spray drying, and the spray drying air inlet temperature is 180°C to 220°C; the sintering temperature is 720°C to 800°C, and the sintering time is 4h to 12h.
8. The method for preparing an alkyl glycoside modified lithium iron phosphate according to claim 4, characterized in that: In the step S4, the doping source gas is at least one of ammonia, diborane and hydrogen sulfide.
9. The method for preparing an alkyl polyglycoside modified lithium iron phosphate according to claim 4, characterized in that: The method further includes step S5: removing the catalyst Fe2O3: washing the modified lithium iron phosphate with an inorganic acid solution to remove Fe2O3.
10. An application of the alkyl glycoside modified lithium iron phosphate according to any one of claims 1 to 3 and the alkyl glycoside modified lithium iron phosphate prepared by the preparation method according to any one of claims 4 to 9, characterized in that: Its application as positive electrode material for lithium batteries.
Citation Information
Patent Citations
Carbon nanotube / lithium iron phosphate composite material and preparation method and application thereof
CN113991072A
Cited By
Gas-phase doped lithium iron phosphate and preparation method thereof
CN121757834A